Nano-film for relieving bone fracture pain and preparation method thereof

By adopting a three-layer nanofilm, combined with electrospinning process and the addition of nanosilica particles, the problems of uncontrollable drug release rate and low drug safety are solved, and more stable drug release and higher drug safety are achieved.

CN119700721AActive Publication Date: 2025-03-28ZHUHAI HOSPITAL OF INTEGRATED TRADITIONAL CHINESE & WESTERN MEDICINE (ZHUHAI SECOND PEOPLES HOSPITAL)

Patent Information

Application Number
CN202510223148.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-03-28
Estimated Expiration
2045-02-27

AI Technical Summary

Technical Problem

In the prior art, the drug release rate is uncontrollable and the safety of drug use is reduced.

Method used

A three-layer structure nanofilm is used, the inner layer, intermediate layer and outer layer are made of mixed Chinese medicine extract and substrate, and are prepared by electrospinning process. Nanosilicon dioxide particles are added to the outer layer to improve moisture resistance and mechanical strength.

Benefits of technology

A more stable membrane structure and a more uniform and stable drug release rate are achieved, and the film's moisture resistance, mechanical strength and drug safety are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a nano-film for relieving bone fracture pain and a preparation method thereof, and relates to the technical field of medical films, the nano-film comprises an inner layer, a middle layer and an outer layer, the three layers are prepared by mixing traditional Chinese medicine extracts and base materials, the nano-film is prepared through an electrostatic spinning technology, the components of all the layers are the same, but the proportions are different, and the inner layer and the middle layer are different. Wherein a polycaprolactone and polyvinyl alcohol blending system is selected as the base material; the inner layer has high drug-loading capacity to quickly relieve symptoms, the middle layer has continuous release, the outer layer has low drug-loading capacity to reduce initial stimulation and increase stability, the use frequency is reduced, the drug effect is prolonged, and adverse reactions are reduced; the functions of protection, slow release and quick release are realized only by adjusting the proportion of PCL / PVA, and the production process is simplified.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical films, and in particular to a nano film for relieving pain from bone injuries and a preparation method thereof. Background Art

[0002] External treatment with traditional Chinese medicine is a treatment method that uses traditional Chinese medicine in different dosage forms and applies it to the body surface, directly acting on local lesions, or stimulating acupoints and meridians and local physical stimulation to achieve the purpose of treating diseases. External treatment with traditional Chinese medicine has unique and effective advantages in treating local surgical lesions. With the rapid development of nanotechnology, its application in the biomedical field is becoming more and more extensive, especially in orthopedic pain relief. As an innovative biomedical material, nanofilms have shown unique advantages in bone pain relief due to their unique physical, chemical and biological properties. Nanofilms are usually composed of nano-scale materials, which show properties that are completely different from macroscopic materials at the microscopic scale. Nanofilms can have extremely high specific surface areas, thereby increasing their ability to interact with other substances. In terms of bone pain relief, nanofilms can play a role through various mechanisms such as loading drugs, promoting tissue regeneration, and inhibiting inflammatory responses.

[0003] For example, the Chinese patent application number CN202210739920.X discloses a method for preparing a Chinese medicine micro-nano fiber film for treating psoriasis and the prepared film, comprising the following steps: (1) preparing an electrostatic spinning solution by mixing several polymers in proportion; (2) adding the Chinese medicine component for treating psoriasis into step (1) by spinning to obtain a Chinese medicine electrostatic spinning solution; (3) transferring the Chinese medicine spinning solution obtained in step (2) to a jet reservoir in an electrostatic spinning device, and preparing a Chinese medicine micro-nano fiber film with a high diameter specific surface area, large porosity, and good air permeability for in vitro application to treat psoriasis by setting a preparation scheme and preparation parameters. The advantage is that it provides a Chinese medicine micro-nano fiber film for external treatment of psoriasis that is low in cost, convenient, directly acts on the affected part, has a fast onset of action, a short course of treatment, is not prone to recurrence, and has no toxic side effects.

[0004] However, good air permeability can easily lead to external bacteria or other contamination, and it is easy to absorb moisture, which leads to a decrease in the mechanical properties of the membrane, and ultimately leads to uncontrollable drug release rate, inability to stabilize the therapeutic effect and difficulty in ensuring the safety of medication. Summary of the invention

[0005] The embodiments of the present application solve the problems in the prior art of uncontrollable drug release rate and reduced drug safety, and achieve a more stable membrane structure and a more uniform and stable drug release rate.

[0006] An embodiment of the present application provides a nanofilm for relieving bone injury pain, including an inner layer, a middle layer, and an outer layer, all of which are made by mixing Chinese medicine extracts and a substrate, and the nanofilm is prepared by an electrospinning process, wherein the substrate is a blend of polycaprolactone and polyvinyl alcohol.

[0007] Further, the specific steps include: S1. Preparation of Chinese herbal medicine extracts, the preparation method is as follows: the Chinese herbal medicines are mixed in proportion, crushed, and then ethanol-water (7:3) is used as a solvent, ultrasonic-assisted extraction is performed twice at 60°C, each time for 1 hour, the extracts are combined, and the extracts are concentrated under reduced pressure to an extract, and the Chinese herbal medicine extract powder is obtained after freeze-drying; S2, preparation of layered electrospinning solution; the base material is a blend system of polycaprolactone and polyvinyl alcohol, and the layered proportioning is performed; S3, layered electrospinning process, using a three-nozzle electrospinning device, suck the prepared electrospinning solution into a sterile syringe, install the needle, remove bubbles, set the voltage, solution push speed, the distance between the needle jet and the receiving device, the spinning temperature and humidity, start spinning, and use a flat plate or roller to receive it to obtain a micro-nano spinning fiber membrane with good uniformity, which is freeze-dried for 24-48 hours for use.

[0008] Furthermore, the ratio of Chinese medicine in step S1 is: 6.2% of Tripterygium wilfordii, 9.7% of Epimedium, 6.5% of Angelica sinensis, 12.9% of Radix Rehmanniae, 6.5% of Rhizoma Chuanxiong, 3.1% of Saffron, 12.9% of Eucommia ulmoides, 6.5% of Frankincense, 6.5% of Myrrh, 9.7% of Achyranthes bidentata, 3.1% of Borneol, 3.5% of Papaya, and 12.9% of Clematis chinensis.

[0009] Furthermore, in step S2, the ratio of each layer is: the outer layer substrate is PCL:PVA = 8:2; the middle layer substrate is PCL:PVA = 5:5; the inner layer substrate is PCL:PVA = 2:8; and the solvent is a mixture of hexafluoroisopropanol and ultrapure water in a ratio of 7:3.

[0010] Furthermore, the outer layer contains Chinese herbal medicine extracts accounting for 20% of the mass of the outer layer.

[0011] Furthermore, the middle layer contains Chinese herbal medicine extract accounting for 30% of the mass of the middle layer.

[0012] Furthermore, the outer layer contains Chinese herbal medicine extracts accounting for 40% of the mass of the inner layer.

[0013] Furthermore, 1% of nano-silicon dioxide particles are added to the outer layer of the film, and the particle size of the nano-silicon dioxide is 10-50nm.

[0014] Furthermore, 2.5% of nano-silicon dioxide particles are also added to the middle layer of the film, and the particle size of the nano-silicon dioxide is 5-20nm.

[0015] Furthermore, the middle layer contains a combination of nano-silicon dioxide particles of different particle sizes, specifically: large particles: 20-50nm; small particles: 5-15nm; large particles: small particles = 3:1.

[0016] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages: First, the high drug loading in the inner layer quickly relieves symptoms, the middle layer releases continuously, and the low drug loading in the outer layer reduces initial irritation, thereby reducing the number of uses, prolonging drug efficacy, and reducing adverse reactions; the "protection-sustained release-fast release" function is achieved only by adjusting the PCL / PVA ratio, simplifying the production process.

[0017] Second, nano-silica has unique surface properties and pore structure. Its particle size is small, its specific surface area is huge, and its surface energy is high, which makes it have strong adsorption capacity. And because of its rich pore structure, it can provide a large number of adsorption sites, which enhances its water absorption performance. After adding nano-silica particles to the outer layer of the film, these particles can absorb moisture in the air and reduce the penetration of moisture into the middle and inner layers, thereby increasing the moisture resistance of the film. And because of its large surface area, it has a higher degree of integration with the substrate in the outer layer, forming physical cross-linking points, improving tensile strength, and increasing the stability of the outer layer. The tear resistance of the film is enhanced and it can be applied repeatedly. Nano-silica has high hardness and high wear resistance. After adding, it can significantly improve the mechanical strength of the film, making it more durable, enhancing the anti-aging and weather resistance of the film, and extending its service life. Silica has good biocompatibility, which can reduce irritation or allergic reactions to the human body.

[0018] Third, the nanoparticles in the outer and middle layers attract each other through physical effects such as van der Waals forces, which affects their distribution and arrangement in the film. The particle size, shape and surface properties of the nanoparticles will affect this physical interaction. Small particles are more likely to agglomerate near large particles, forming a tighter stacking structure at the junction of the outer and middle layers; this can not only further prevent moisture from entering the middle and inner layers, but also increase the interface bonding strength and stability.

[0019] Fourth, large and small particles form a denser network through geometric complementarity, which enhances the barrier property of the film; small particles have a high specific surface area to adsorb more drug molecules and delay the initial burst release; large particles extend the drug diffusion path and work together with small particles to achieve linear release, so that drug molecules need to bypass the "maze-like" channels formed by large and small particles, increasing the diffusion resistance; the initial burst release is reduced and the mid-term sustained release is linearized. DETAILED DESCRIPTION

[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.

[0021] Embodiment 1: A nanofilm for relieving pain from bone injuries, comprising: an inner layer, a middle layer, and an outer layer; specifically, the inner layer is a quick-release layer, the middle layer is a sustained-release layer, and the outer layer is a protective layer, and the materials used in each layer are the same but in different proportions; The film is made by electrospinning the substrate mixed with Chinese medicine extracts in layers. The preparation method is as follows: S1. Preparation of Chinese herbal medicine extracts, the preparation method is as follows: the Chinese herbal medicines are mixed in proportion, crushed, and then ethanol-water (7:3) is used as a solvent, ultrasonic-assisted extraction is performed twice at 60°C, each time for 1 hour, the extracts are combined, and the extracts are concentrated under reduced pressure to an extract, and the Chinese herbal medicine extract powder is obtained after freeze-drying; The Chinese medicine ratio is: 12.9% Clematis, 6.5% Angelica, 12.9% Rehmannia, 6.5% Chuanxiong, 3.1% Crocus, 12.9% Eucommia, 6.5% Frankincense, 9.7% Epimedium, 6.5% Myrrh, 9.7% Achyranthes, 3.1% Borneol, 3.5% Papaya, 6.2% Tripterygium wilfordii. S2. Preparation of layered electrospinning solution: The base material is a blend of polycaprolactone (PCL) and polyvinyl alcohol (PVA), and the layered proportions are as follows: The outer layer is PCL:PVA = 8:2 + Chinese herbal medicine extract (20%); The middle layer is PCL:PVA = 5:5 + Chinese herbal medicine extract (30%); The inner layer is PCL:PVA = 2:8 + Chinese herbal medicine extract (40%); The solvent was a mixture of hexafluoroisopropanol and ultrapure water in a ratio of 7:3; S3, layered electrospinning process, specifically: using a three-nozzle electrospinning device, sucking the prepared electrospinning solution into a sterile syringe, installing the needle, removing bubbles, setting the voltage, solution pushing speed, the distance between the needle jet and the receiving device, the spinning temperature and humidity, starting spinning, using a flat plate or a roller to receive, obtaining a micro-nano spinning fiber membrane with good uniformity, and freeze-drying for 24-48 hours for use; The process parameters are shown in Table 1:

[0022] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: Through the layered structure design, the outer layer uses a high PCL ratio to form a hydrophobic dense network to increase stability, and forms a microporous structure (porosity 50%-60%, pore size 0.5-1μm) through high voltage and low push speed, with good air permeability (WVTR≥700 g / m²·24h); the middle layer uses PCL and PVA blends to balance hydrophobicity / hydrophilicity, and the drug is synergistically released through PVA swelling and PCL degradation (60% of the drug is released in 72 hours); the inner layer uses a high PVA ratio to quickly absorb water and swell, and the drug is released by 50% within 1 hour, and it takes effect quickly after being attached to the skin; The high drug loading in the inner layer quickly relieves symptoms, the middle layer releases continuously, and the low drug loading in the outer layer reduces initial irritation, thus reducing the number of uses, prolonging the efficacy, and reducing adverse reactions; The “protection-sustained-release-immediate-release” function can be achieved by simply adjusting the PCL / PVA ratio, thus simplifying the production process; Traditional Chinese medicine ingredients achieve synergy of anti-inflammatory and repair. Clematis, Tripterygium wilfordii, and Epimedium inhibit inflammatory factors and improve immunity; frankincense and myrrh promote wound healing; borneol and saffron act as transdermal enhancers to improve drug penetration efficiency; The average fiber diameter was measured by microscope, the porosity was calculated by nitrogen gas adsorption method, the drug release was tested in physiological saline, the transdermal rate was tested by transdermal absorption test using simulated pig skin at 37°C and 80% humidity, the tensile strength was tested using GB / T 1040.3-2006, and the films of different layers were tested respectively. The results are shown in Table 2:

[0023] Example 2: The above example achieves the "protection-sustained release-quick release" function by adjusting the PCL / PVA ratio to simplify the production process. However, in actual use, it is found that the outer layer has more voids, which increases the breathability while also increasing the moisture absorption capacity. Although the outer layer has higher stability, the middle layer and the inner layer will swell and reduce the efficacy due to moisture in the air, ultimately leading to reduced efficacy and shortened film life. In order to increase moisture resistance, further improvements are made on the basis of Example 1.

[0024] The outer layer of the film also contains 1% nano-silicon dioxide particles with a particle size of 10-50nm; The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: Nano-silicon dioxide has unique surface properties and pore structures. Its particle size is small, its specific surface area is huge, and its surface energy is high, which makes it have strong adsorption capacity. And because of its rich pore structure, it can provide a large number of adsorption sites, which enhances its water absorption performance. After adding nano-silicon dioxide particles to the outer layer of the film, these particles can absorb moisture in the air and reduce the penetration of moisture into the middle layer and the inner layer, thereby increasing the moisture resistance of the film (the contact angle increases from 112° to 127°); and because of the large surface area, the degree of bonding with the substrate in the outer layer is higher, forming physical cross-linking points, improving the tensile strength (from 4.2 MPa to 5.5 MPa), and increasing the stability of the outer layer; the tear resistance of the film is enhanced, and it can be applied repeatedly; Nano-silica has high hardness and high wear resistance. After adding, it can significantly improve the mechanical strength of the film, making it more durable, enhancing the film's anti-aging and weather resistance, and extending its service life. Silica has good biocompatibility and can reduce irritation or allergic reactions to the human body.

[0025] Embodiment 3: Embodiment 2 improves moisture resistance by adding nano-silicon dioxide to the outer layer. To further improve the interlayer bonding, nano-silicon dioxide is also added to the middle layer on the basis of Embodiment 2.

[0026] 2.5% of nano-silicon dioxide particles are also added to the middle layer of the film, and the particle size of the nano-silicon dioxide is 5-20nm; The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: Small-particle nano-silica forms microchannels in the PCL / PVA matrix. Through the adsorption-desorption effect, the drug molecules are adsorbed on the surface, delaying the initial burst release, hindering the diffusion path of drug molecules, achieving linear release, and more stable sustained release; and further improving moisture resistance, with a 1h expansion rate of 9.7% in a humidity environment of 85%; The nanoparticles in the middle layer form hydrogen bonds / van der Waals forces with the inner and outer layer materials, increasing the interface bonding strength by 20%; In addition, the surface of nano-silica is modified with hydroxyl groups to destroy bacterial cell membranes (the antibacterial rate for Staphylococcus aureus is ≥70%); it can also inhibit the movement of polymer chain segments, and the thermal decomposition temperature of the film is increased from 220°C to 250°C; The nanoparticles in the outer and middle layers attract each other through physical effects such as van der Waals forces, which affects their distribution and arrangement in the film. The particle size, shape and surface properties of the nanoparticles will affect this physical interaction. Small particles are more likely to agglomerate near large particles, forming a tighter stacking structure at the junction of the outer and middle layers; this can not only further prevent moisture from entering the middle and inner layers, but also increase the interface bonding strength and stability.

[0027] The tensile strength and drug release capacity of the film were tested, and the results are shown in Table 3;

[0028] Example 4: Example 3 not only enhances moisture resistance but also further optimizes the sustained release capability by adding nanoparticles into the middle layer. To further optimize the particle distribution, further improvements are made on the basis of Example 3.

[0029] The middle layer contains a combination of nano-silicon dioxide particles of different particle sizes, specifically: large particles: 20-50nm; small particles: 5-15nm; large particles: small particles = 3:1 (mass ratio).

[0030] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: The large particles in the middle layer serve as the skeleton support to form the main structure; the small particles fill the gaps between the large particles, reducing the porosity (to 35%) and complicating the water penetration path; Large and small particles form a denser network through geometric complementarity, enhancing the barrier property of the film; small particles have a high specific surface area to adsorb more drug molecules, delaying the initial burst release; large particles extend the drug diffusion path and work together with small particles to achieve linear release (the 72-hour release rate is optimized from 53% to a more stable 50%), so that drug molecules need to bypass the "maze-like" channel formed by large and small particles, increasing the diffusion resistance; the initial burst release is reduced (the inner layer release in 1 hour is from 50% to 40%), and the mid-term sustained release is linearized (the 24-hour middle layer release is from 29% to 26%); Large particles disperse stress and improve tear resistance; small particles fill defect sites and improve tensile strength. Large and small particles form a "rigid and flexible" structure through physical cross-linking, which improves strength and tear resistance. The mixed particles in the middle layer form a gradient interface with the inner layer (high PVA) and the outer layer (high PCL + large particles) through van der Waals forces and hydrogen bonds; the large particles in the outer layer are interlocked with the large particles in the middle layer, and the small particles in the middle layer can penetrate into the PVA network in the inner layer; the outer layer and the middle layer are interlocked, and the small particles in the inner layer are attracted by the large particles in the middle layer, thereby strengthening the three-layer structure and the interface bonding force.

[0031] The dense structure of the middle layer reduces the reverse penetration of water to the outer layer, delaying the hydrolysis of the outer layer PCL; the gradient distribution of particles (large particles in the outer layer → mixed particles in the middle layer → a small amount of small particles that penetrate the inner layer) forms a continuous barrier, improving moisture resistance (film expansion rate <5% at 85% humidity); the densification of the middle layer reduces the moisture absorption and expansion of the inner layer, maintaining a high porosity of the inner layer (64% → 62%), ensuring that the rapid release function is not affected by deliquescence.

[0032] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A nanofilm for relieving pain from bone injuries, characterized in that: The inner layer, the middle layer and the outer layer are all made of a mixture of Chinese herbal medicine extracts and a base material, and the nano-film is prepared by an electrospinning process. The components of each layer are the same, but the proportions are different. The base material is a blend of polycaprolactone and polyvinyl alcohol.

2. A method for preparing a nanofilm for relieving bone pain as claimed in claim 1, characterized in that: The specific steps include: S1. Preparation of Chinese herbal medicine extracts, the preparation method is as follows: the Chinese herbal medicines are mixed in proportion, crushed, and then ethanol-water (7:3) is used as a solvent, ultrasonic-assisted extraction is performed twice at 60°C, each time for 1 hour, the extracts are combined, and the extracts are concentrated under reduced pressure to an extract, and the Chinese herbal medicine extract powder is obtained after freeze-drying; S2, preparation of layered electrospinning solution; the base material is a blend system of polycaprolactone and polyvinyl alcohol, and the layered proportioning is performed; S3, layered electrospinning process, using a three-nozzle electrospinning device, sucking the prepared electrospinning solution into a sterile syringe, installing the needle, removing bubbles, setting the voltage, solution push speed, the distance between the needle jet and the receiving device, the spinning temperature and humidity, starting spinning, using a flat plate or a roller to receive, to obtain a micro-nano spinning fiber membrane with good uniformity, freeze-dried for 24-48 hours for use, the process parameters are: Outer layer: voltage 20KV, push speed 0.05mm / min, receiving distance 18cm, 25℃, 30% humidity; Middle layer: voltage 15KV, push speed 0.1mm / min, receiving distance 15cm, 25℃, 40% humidity; Outer layer: voltage 10KV, push speed 0.2mm / min, receiving distance 12cm, 25℃, 50% humidity.

3. The method for preparing a nano film for relieving bone pain as claimed in claim 2, characterized in that: The proportion of Chinese medicine in step S1 is: 6.2% of Tripterygium wilfordii, 9.7% of Epimedium, 6.5% of Angelica sinensis, 12.9% of Radix Rehmanniae, 6.5% of Rhizoma Chuanxiong, 3.1% of Crocus sativus, 12.9% of Eucommia ulmoides, 6.5% of Frankincense, 6.5% of Myrrh, 9.7% of Achyranthes bidentata, 3.1% of Borneol, 3.5% of Papaya, and 12.9% of Clematis chinensis.

4. The method for preparing a nano film for relieving bone pain as claimed in claim 2, characterized in that: The ratio of each layer in step S2 is: the outer layer substrate is PCL:PVA = 8:2; the middle layer substrate is PCL:PVA = 5:5; the inner layer substrate is PCL:PVA = 2:8; the solvent is a mixture of hexafluoroisopropanol and ultrapure water in a ratio of 7:

3.

5. The method for preparing a nano film for relieving bone pain as claimed in claim 4, characterized in that: The outer layer contains Chinese herbal medicine extracts accounting for 20% of the outer layer mass.

6. The method for preparing a nano film for relieving bone pain as claimed in claim 4, characterized in that: The middle layer contains Chinese herbal medicine extracts which account for 30% of the weight of the middle layer.

7. The method for preparing a nano film for relieving bone pain as claimed in claim 4, characterized in that: The outer layer contains Chinese herbal medicine extracts which account for 40% of the mass of the inner layer.

8. The method for preparing a nano film for relieving bone pain as claimed in claim 4, characterized in that: 1% of nano-silicon dioxide particles are also added to the outer layer of the film, and the particle size of the nano-silicon dioxide is 10-50nm.

9. The method for preparing a nano film for relieving bone pain according to claim 8, characterized in that: 2.5% of nano-silicon dioxide particles are also added to the middle layer of the film, and the particle size of the nano-silicon dioxide is 5-20nm.

10. The method for preparing a nano film for relieving bone pain according to claim 8, characterized in that: The middle layer contains a combination of nano-silicon dioxide particles of different particle sizes, specifically: large particles: 20-50nm; small particles: 5-15nm; large particles: small particles = 3:1.

Citation Information

Patent Citations

  • Multi-layer drug sustain-release nano fiber membrane and preparation method thereof

    CN103599090A

  • Production method of medicine-carried polycaprolactone-chitosan-silica hybrid fibers

    CN111821463A

  • Preparation method of traditional Chinese medicine micro-nanofiber film for treating psoriasis and prepared film

    CN114960028A

  • Sandwich-like structure drug-loading micro-nanofiber composite membrane medical dressing and preparation method thereof

    CN117860945A

  • Transdermal absorbed medicine for treating periarthritis of shoulder joint

    CN1336196A

Cited By

  • Wear-resistant nanofiber reinforced protective graphene fiber as well as preparation method and application thereof

    CN119900120A

  • Wear-resistant nanofiber-reinforced protective graphene fibers and their preparation methods and applications

    CN119900120B